Promote forest rights reforms essential to achieving goal of 350 million hectares of degraded forests restored globally by 2030 - CGIAR Research Program on Policies, Institutions, and Markets (2017)
CIFOR research supported by PIM and carried out in 2017 demonstrates that unless farmers and communities have secure rights to forests it is unlikey they will invest in forest landscape restoration (FLR) activities over the long term. GIZ, the German development agency, adopted CIFOR recommendations that interventions clarifying forest rights accompany FLR initiatives. In 2018 CIFOR with GIZ and PIM funding will be advising GIZ programs in Madagascar and Ethiopia on linking FLR interventions with measures to enhance tenure security.